TUTUPAN LAHAN GAMBUT MEMPENGARUHI KONDISI IKLIM MIKRO DI SEKITAR KAMPUS UNIVERSITAS PALANGKA RAYA (Preliminary Data Integrasi Wireless Sensor Network) The Peatland Cover Impact Micro Climate Conditions Near Campus of the University of Palangka Raya (Preli: Adji, F.A.,1*) dan Teguh, R.,2) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThe lack of field measurements, which collected in long period and significantly spatial effect onthe environments can obstruct scientific understanding the effect of environmental condition on theecosystems. Application wireless sensor network (WSN) is useful to address the situation throughlow cost wireless measurement sensors and minimize disruption to the location/conditions to bemonitored. The comprehension of composition transformation, structure, the environmentecosystems dynamic, and how is the transformation of all can be affecting the human life, indeedthis challenge are need detail analysis of all environment ecosystem elements. This study alsoreview the uses of smart devices wireless sensor networks (WSN), and observe the underlyingtechnology in hopes could be giving solve or determine the condition of environment andecosystems affected by human activity. The results of this study showed that the land use cover isinfluence on the environment conditions.Keywords: Wireless sensor networks (WSN), ecosystems, and environment